Hubungan Praktik Kebersihan Diri Terhadap Kejadian Stunting Pada Anak Balita - Hasrul Hasrul; Aslinda Hafid (Jurnal Keperawatan Muhammadiyah, 2023)
Objective: Stunting resulting from chronic malnutrition and infections over 1000 especially during the first days of life (HPK). The fetus to the 23 months old.  Children are stunting when the length or height has been under minus two standard deviations seumurnya the length or height (Hasrul et al., 2020).   Future generations the nation today have to under fives so needs special attention  (H. Hasrul & Nurdin, 2020).  The purpose of this research look at the relationship the foster parents in terms of hygiene practices to his son to events stuntingMethods:  Research methodology use observational with the design research case control.  It is a whole population in research families that have toddlers to in the work area of Puskesmas Lawawoi. The sample tehnik systemic in random sampling Obtained a total of 102 Children under five The children as many as 51 stunting (Case) and As many as children who are not stunting 51 (Control)Results:  This research has been carried out in Kelurahan Batu Lappa  working area UPT Puskesmas Lawawai  as much 102 sampel.  Results of the study show there is a link between self-hygiene practices with stunting events shown by the p-value  = 0,016 and OR = 3,42  Which means cleaning practices downside risk having himself  3,42 times  Higher to be stunting than good self-cleaning practicesConclusion: a  connection self-hygiene against  Stunting incident in children under five